Coordination polymers of Cu(II), Co(II) and Cd(II) based on a tetramethyl-substituted terphenyldicarboxylic acid. (15th September 2019) - Dascalu, Ioan-Andrei; Shova, Sergiu; Dumitrescu, Dan Gheorghe; Roman, Gheorghe; Bratanovici, Bogdan-Ionel; Ardeleanu, Rodinel; Lozan, Vasile
Graphical abstract: Coordination polymers of 2′, 3′, 5′, 6′-tetramethyl-[1, 1′:4′, 1′′-terphenyl]-4, 4′′-dicarboxylic acid with Cu(II), Co(II) and Cd(II) have been synthesized and characterized by IR spectroscopy, single crystal X-ray diffraction, thermogravimetric analysis and nitrogen sorption studies. Abstract: Three new 3D-metal–organic frameworks based on 2′, 3′, 5′, 6′-tetramethyl-[1, 1′:4′, 1′′-terphenyl]-4, 4′′-dicarboxylic acid (H2 L) and Co, Cu, and Cd nodes have been synthesized. The complexes were characterized by elemental, thermogravimetric analysis, IR spectroscopy, single crystal, powder X-ray diffraction and gas sorption experiments. The crystal structure of [Cu2 L2 (H2 O)2 ] n (1 ) corresponds to a two-dimensional coordination polymer, in which the metal nodes are two crystallographically equivalent Cu(II) atoms linked by four μ2 -O, O′ carboxylate ligands in a centrosymmetric Cu2 O10 paddle-wheel building block. The structure of compound [CoL(dmso)] n (2 ) has a 3D metal–organic coordination lattice, in which the metal centers are connected by the linear organic ligand to generate a dense three-dimensional coordination polymer. Also, a three-dimensional coordination network was identified in the case of compound [Cd2 L2 (dmf)] n (3 ), whose structure is very similar to that of compound2 . In compound3, the carboxylate groups of the linear L 2− spacers behave as μ2 - κ 3 O, O′:O tridentate bridging ligands. The compounds have a high thermal stability. Polymers3 and1 have moderate porosity (specific surface areas of approximately 900 m 2 /g and 600 m 2 /g, respectively), while polymer2 has a dense structure.